Multiplicative (generalized)-derivations of prime rings that act as $n$-(anti)homomorphisms - G.S. Sandhu (Математичні Студії, 2020)
Let R be a prime ring. In this note, we describe the possible forms of multiplicative (generalized)-derivations of R that act as n-homomorphism or n-antihomomorphism on nonzero ideals of R. Consequently, from the given results one can easily deduce the results of Gusić ([7]).